2014
DOI: 10.1021/np401025f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Inflammatory Activity of Prenylated Substances Isolated from Morus alba and Morus nigra

Abstract: Chromatographic separation of root extracts of Morus alba and M. nigra led to the identification of the 2-arylbenzofurans moracin C (1), mulberrofuran Y (2), and mulberrofuran H (3), and the prenylated flavonoids kuwanon E (4), kuwanon C (5), sanggenon H (6), cudraflavone B (7), and morusinol (8), and the Diels-Alder adducts soroceal (9), and sanggenon E (10). The cytotoxicity and their antiphlogistic activity, determined as the attenuation of the secretion of TNF-α and IL-1β and the inhibition of NF-κB nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 51 publications
0
67
0
Order By: Relevance
“…Morus alba L. and Morus nigra L. (both known as mulberry) are deciduous trees belonging to the family Moraceae (Zelová et al, 2014). Mulberry plants have edible and tasty fruits, while various plant parts have been used in traditional Chinese medicine for centuries.…”
Section: Introductionmentioning
confidence: 99%
“…Morus alba L. and Morus nigra L. (both known as mulberry) are deciduous trees belonging to the family Moraceae (Zelová et al, 2014). Mulberry plants have edible and tasty fruits, while various plant parts have been used in traditional Chinese medicine for centuries.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the extract tested was prepared from leaves [10, 11, 14] and root bark [12, 13, 15]. In our study, anti-inflammation activity of the extract prepared from mulberry stems was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…M. alba extract has been demonstrated to exhibit anti-inflammatory activity, through the inhibition of iNOS, NO, and COX [1015]. However, most of the extract tested was prepared from leaves [10, 11, 14] and root bark [12, 13, 15].…”
Section: Resultsmentioning
confidence: 99%
“…Mulberry has been used as a traditional medicine in East Asia for the prevention of insomnia, dizziness, and tinnitus as well as the alleviation of high glucose levels (8,9). Previous researches have reported that various chemical constituents and extracts from this natural source exhibit useful pharmacological activities including anti-inflammatory, antioxidant, and immunoregulative effects (10)(11)(12). A recent study reported that anthocyanin-rich mulberry extracts alleviate high glucose levels in in vivo studies of glucose consumption and uptake, which was attributed to AMPK/ACC/mTOR signaling (13).…”
Section: Introductionmentioning
confidence: 99%